Developing the Student Anchor Engagement Framework - Jennifer Johnson Kebea (Coalition of Urban and Metropolitan Universities, 2019)
Modern urban and metropolitan universities are increasingly obliged to recognize their role as anchor institutions. These same institutions of higher education (IHEs) also have a responsibility to educate students to be responsible and participatory citizens in society. An increasing number of IHEs recognize these distinct commitments as central to the public purpose of higher education. However, few intentionally involve students in anchor mission work. This misalignment denies students a rich opportunity for civic learning and democratic engagement. Furthermore, it prevents IHEs and their surrounding communities from realizing the benefits of harmonizing these two commitments. This mixed-methods research study resulted in the development of the Student Anchor Engagement Framework, a 36-item strategic framework designed to identify how IHEs can intentionally involve students in anchor strategy. The framework derives from The Democracy Collaborative's Anchor Institution Community Benefit Dashboard. Expert participants ranked all items included in the framework as to their potential to influence student civic learning and democratic engagement. Implications of this research study include the potential for IHEs to consider, strategically, ways to align student civic learning with anchor institution practices for the advancement of both pursuits.